MEANINGFUL WORK AND EMPLOYEE ENGAGEMENT ON EMPLOYEES: A META-ANALYSIS - Fauzi, Argita Maya; Ancok, Djamaluddin; Rahardjo, Wahyu (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
Some of previous published research has shown a correlation between meaningful work and employee engagement. However, there is no research that reveals how true r and size effect are from the correlation of the two variables. This meta-analysis aims to measure the correlation between meaningful work and employee engagement by considering the effect size. The total sample of this research is 5281 people from 10 studies who are a significant positive correlation with employee engagement at a high level with 95% CI (0.681; 1.004). Furthermore, the result show that good in heterogeneity test and there was no publication bias,